2000
DOI: 10.1086/312578
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Structure of the Carina Nebula

Abstract: Observations obtained with the Midcourse Space Experiment (MSX) satellite reveal for the first time the complex mid-infrared morphology of the entire Carina Nebula (NGC 3372). On the largest size scale of ∼100 pc, the thermal infrared emission from the giant H ii region delineates one coherent structure: a (somewhat distorted) bipolar nebula with the major axis perpendicular to the Galactic plane. The Carina Nebula is usually described as an evolved H ii region that is no longer actively forming stars, clearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
149
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(154 citation statements)
references
References 21 publications
5
149
0
Order By: Relevance
“…We can see many of them in the southern part of the image. We also observe large bubbles in the northern region, probably caused by the gusts of hot gas leaking from the powerful stars at the center of the nebula (Smith et al 2000). The central clusters Tr 14 and Tr 16 tend to be devoid of star formation (Smith & Brooks 2008), but there are active sites of ongoing star formation in the outer regions of the nebula.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We can see many of them in the southern part of the image. We also observe large bubbles in the northern region, probably caused by the gusts of hot gas leaking from the powerful stars at the center of the nebula (Smith et al 2000). The central clusters Tr 14 and Tr 16 tend to be devoid of star formation (Smith & Brooks 2008), but there are active sites of ongoing star formation in the outer regions of the nebula.…”
Section: Introductionmentioning
confidence: 85%
“…However, following the detection of several embedded IR sources, Smith et al (2000) showed that star formation is still going on in this region. Later, Brooks et al (2001) also identified two compact Hii regions possibly linked with very young O-type stars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These HII regions are seen in many massive molecular clouds and are the object of a great number of observational studies: in the Rosette nebula (Schneider et al 2010), M16 (Andersen et al 2004), 30 Doradus (Walborn et al 2002), Carina nebula (Smith et al 2000), the Elephant Trunk nebula (Reach et al 2004), the Trifid nebula (Lefloch et al 2002), M17 (Jiang et al 2002), or the Horsehead nebula (Bowler et al 2009). Spitzer observations also provide a wide range of HII regions, which were studied in detail by Deharveng et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…through jets from obscured proto-stars piercing through the surface into the HII region (e.g. in Eta Carina, Smith et al 2000).…”
Section: Introductionmentioning
confidence: 99%